Presentations for From Commitments to Impact: Analyzing the Global Commitments Toward Promoting Food Security and Healthy Diets - Zorbas, Christina; Suri, Shoba; Iruhiriye, Elyse; Menon, Purnima; Vos, Rob (2024)
Since the mid-2010s, progress in reducing food insecurity and improving diet quality has stalled. Multiple shocks, including the COVID-19 pandemic, climate change, and Russia’s invasion of Ukraine in 2022, have exacerbated the situation and put Sustainable Development Goal 2 on Zero Hunger further out of reach.